Suprascapular Nerve Block: A Technical Review - Himanshu Agrawal; Chandrakant Pilania; Nitesh Manohar Gonnade (Indian Journal of Physical Medicine & Rehabilitation, 2023)
Suprascapular nerve block (SSNB) is a safe and effective method to treat pain in chronic diseases that affect the shoulder, such as irrecoverable injury of rotator cuff, rheumatoid arthritis, calcific tendinitis, cancer, stroke sequels and adhesive capsulitis. SSNB has been applied in the management of acute and chronic shoulder pain as well as for the diagnosis of suprascapular neuropathy. Since this procedure is very handy for physiatrist and pain physicians, here we tend to provide the basic anatomy of the nerve and associated structures along with the review of the basic techniques described in literature with the insights of the author for the same.